Exploring the effect of silicene monolayer on the structure and function of villin headpiece and amyloid fibrils by molecular dynamics simulations. Issue 1 (11th September 2020) - Meng, Yajie; Liu, Ruirui; Song, Liting; Zhu, Min; Zhai, Honglin; Ren, Cuiling
Abstract: With the development of various nanomaterial expected to be used in biomedical fields, it is more important to evaluate and understand their potential effects on biological system. In this work, two proteins with different structure, Villin Headpiece (HP35) with α‐helix structure and protofibrils Aβ1‐42 with five β‐strand chains, were selected and their interactions with silicene were studied by means of molecular dynamics (MD) simulation to reveal the potential effect of silicene on the structure and function of biomolecules. The obtained results indicated that silicene could rapidly attract HP35 and Aβ1‐42 fibrils onto the surface to form a stable binding. The adsorption strength was moderate and no significant structural distortion of HP35 and Aβ1‐42 fibrils was observed. Moreover, the strength of calculated the H‐bonds in neighbor chain of Aβ1‐42 fibrils indicated that the mild interactions between silicene and fibrils could regularize the structure of Aβ1‐42 fibrils and stabilize the interactions between five chains of fibrils protein, which might enhance the aggregation of Aβ1‐42 fibrils. This study provides a new insight for understanding the interaction between nanomaterials and biomolecules and moves forward the development of silicene into biomedical fields.